Metal transfer modes in plasma Wire plus Arc additive manufacture - Rios Contesse, Sergio Eduardo; Colegrove, Paul A.; Williams, Stewart W. (My University, 2019)
The stability of Plasma transferred arc Wire + Arc Additive Manufacture is critically dependent on the transfer mode of the wire into the melt pool which can either be in permanent contact (TM1), intermittent (TM2) or fleeting (TM3) and it's governed by the position of the wire. Analysis of the voltage waveforms in conjunction with video imaging was used to understand the preferred mode for process control and how these transfer modes are affected by convex and concave melt pools shapes. The study indicated that stable transfer can be more easily achieved with the convex weld pool, because it minimises the extent of the undesirable TM3 where droplet transfer occurs in an erratic fashion. Furthermore, even though the operational range of TM2 is limited, a control algorithm could be more easily developed for this transfer mode. Finally, video imaging showed how the melt pool oscillation interacts with droplet detachment under some operational conditions.
Keywords: wire plus arc additive manufacture; process control; arc voltage